The promotion of an agricultural syste with sustainable technology elements, the use of vegetable residues and green fertilizers for maize cultivatoin in the Transylvania hills - Felicia Cheţan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The paper presents the results of research conducted under the conditions of Turda Agricultural Research and Development Station (ARDS Turda) located in the hill area of Transylvania, regarding the influence of the soil tillage system (CS - plow, MC - minimum chisel, MD - minimum disk and NT - direct sowing), the vegetable residues and the fertilization system on maize yield, in the period 2019, 2020. The systems MD (6430 kg/ha) and NT (5421 kg/ha) negatively influence the yield of maize, the differences from the control (SC 8779 kg/ha) being between 2260 kg/ha - 3239 kg/ha. The yield average achieved in MC(8653 kg/ha) with a difference of 126 kg/ha, does not present statistical assurance. The technological variant with 2.5 t/ha vegetable residues + 350 kg/ha NPK proved to be more efficient in obtained the yield, compared to the variants without mineral fertilizers (vegetable residues + mustard green fertilizer; vegetable residues + gulle).
Keywords: Q01; Q15; Q16; 330; vegetable residues; tillage systems; fertilization; yield; maize